HERMENEUTIC RESPONSIBILITY IN POLITICAL JUDGEMENT. RETRIEVING FACTUAL TRUTH FROM DIRECT INTERACTION - CIOFLEC, Eveline (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
In this paper, I am arguing for hermeneutic responsibility in political judgment, as it can be attributed to Arendt’s work. Political judgment is reflective judgment relying on representation by imagination and therefore only has exemplary validity. Along the line of Arendt’s Lectures on Kant’s Political Philosophy, I point out her argument for a different generality in politics than the generality of concepts. This generality of political judgment always refers back to the particular. Only by this reference to the particular, namely to facts and situations of direct interaction, can the spectator, who undertakes the political judgment, create the public realm where action takes place. However, this task attributed to the spectator also implies the task of reshaping the public realm. These acts of giving an account of and reconsidering all over again facts handed over by narration and testimony imply the hermeneutic responsibility to unceasingly retrieve factual truth which is rooted in direct interaction.